EFFECTIVENESS OF TGT ASSISTED BY QUIZIZZ PAPER MODE ON CRITICAL THINKING SKILLS AND SCIENTIFIC ATTITUDES OF STUDENTS ON ENERGY TOPICS - Maulida Fitriya; Arif Billah (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2024)
This study aims to analyze the effectiveness of the Teams Games Tournament (TGT) model assisted by Quizizz Paper Mode media on energy topic on students' critical thinking skills, and determine the scientific attitude of students through the application of the TGT model assisted by Quizizz Paper Mode media on energy topic in class VIII junior high school. This study used a quantitative true experimental method with a control group pretest-posttest design. Data were collected through pretest and posttest results, scientific attitude questionnaire, and learning implementation observation sheet. Based on the results of the test data analysis with an independent sample t-test, we obtained t_count 2.86 > t_table 2.018 with a significance value of 0.007 < 0.05, it can be concluded that H_0 is rejected and H_1 is accepted. The analysis of the scientific attitude questionnaire obtained an average percentage of students' scientific attitudes of 78% (high category). It can be concluded that the TGT model assisted by Quizizz Paper Mode media on energy topic is effective on critical thinking skills and has a good impact on the scientific attitude of students. The application of TGT assisted by Quizizz Paper Mode media can help students understand the use of Quizizz Paper Mode digital media that can be applied to other topics.